Analytical Survey on the Security Framework of Cyber-Physical Systems for Smart Power System Networks - Ali Al-Jumaili A.H.; Muniyandi R.C.; Hasan M.K.; Singh M.J.; Siaw Paw J.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cybersecurity; Distributed computer systems; Electric power system interconnection; Embedded systems; Network security; Renewable energy resources; Smart power grids; System stability; Cloud-computing; Cybe-physical integrated security; Cybe-physical systems; Cyber physicals; Cyber-physical systems; Networks security; Physical power; Power; Power system; Power systems security; Cyber Physical System